Self-regulation and performance among elite youth soccer players: the role of approach-avoidance motivation - Hamoud, Mounir; Sæther, Stig Arve; Bjørnebekk, Gunnar (Frontiers in Psychology, 2024)
Introduction and methods This study aimed to investigate the motivational processes behind self-regulated learning and performance among 192 soccer players (82 girls) for three age groups (14–16 years old) eligible for the Norwegian national football team. A conditional process model was proposed and tested with achievement goals as mediators between achievement motives on the one hand and coach-reported performance and self-regulated learning on the other hand. The probability of success was examined as a potential moderator in the motivational process. Results As predicted, motives to achieve success directly influenced planning and reflection/evaluation, whereas the influence of the success motive on regulation of effort was explained partly by task- and self-based approach goals. The motive to achieve success was, however, particularly crucial for maintaining these beneficial regulatory processes when the probability of success was found to be from moderate to low. Concerning the avoidance paths, the data supported only some of our original hypotheses. The motive to avoid failure predicted all three types of avoidance-based (task, self, and other) and other-based approach goals but did not contribute to explaining planning, reflection/evaluation, regulation of effort, or performance. There were no significant correlations between motivation variables and coach-reported performance. Moreover, girls were more motivated to avoid failure than boys, while both sexes achieved similar scores for football-specific self-regulated learning, probability of success, achievement goals, and motive to achieve success. Discussion The results are discussed considering a hierarchical motivation model.